Sustaining Yield of Wheat Crop Using Tractor Wheel Compaction and Fertilizer Placement at Ridge Bed Irrigation System - Vistro, Rahim Bux; Talpur, Mashooque Ali; Shaikh, Irfan Ahmed; Mangrio, Munir Ahmed; Soomro, Shakeel Ahmed; Soothar, Rajesh Kumar; Khokhar, Zainulabidin; Khan, Zaheer Ahmed; Chohan, Muhammad; Pahnwar, Riaz Noor (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The population of Pakistan is increasing at an alarming rate, leading to a high demand for more food and fiber production. To address this demand, effective land and water management is required, emphasizing improvement in irrigation and fertilizer use efficiencies of conventional irrigation methods. This study therefore aimed to determine the impact of various tractor wheel compaction and fertilizer placement at ridge bed irrigation method on different soil textures during 2017-18 and 2018-19 at Sindh Agriculture University, Tandojam, Pakistan. The several levels of compaction observed were, without compaction (T1), three-round tractor wheel compactions (T2), and six-round wheel compactions (T3), while the soil textures were clay loam (CL), silty clay loam (SCL), and silty loam (SL). The field trials were conducted in spilt plot in a randomized complete block design (RCBD) with three replications. The results showed that different treatments significantly affected plant growth, yield of wheat, water productivity, and net returns with ridge bed furrow irrigation method. Further, results showed that all parameters significantly increased with increasing soil compaction levels in all soil textures. Based on the results, it was concluded that T3 integrated with fertilizer application at the top of the ridge bed was the most promising method for enhancing the water and fertilizer use efficiency for the wheat crop.